1985
DOI: 10.1148/radiology.154.3.3969487
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high-strip-density radiographic grids: a new antiscatter technique for mammography.

Abstract: We conducted a comprehensive study on the application of ultra-high-strip-density (UHSD) grids to mammography for the improvement of image contrast. These UHSD grids have strip densities of 70 to 100 lines/cm. After investigating the performance of mammographic grids with various design parameters through Monte Carlo simulation studies, we made prototypes of UHSD grids having lead strip thicknesses of 20 to 37 micron, aluminum interspacer thicknesses of 80 to 120 micron, and grid ratios of 2 to 6. The UHSD gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 1 publication
1
14
2
Order By: Relevance
“…Although aluminum-interspaced grids are not used in modern mammography systems, comparison with the results of the study by Chan et al serves as validation of this technique and also lends perspective to why aluminum should not be used. Like Rezentes et al (6), Chan et al (2) reported two different measurement techniques for determining CIF and BF, and the results of both are illustrated in Figure 6. Compared with Chan et al's "transmission" measurement technique, the average difference with our results was 26.9%, and the "phantom" measurement technique differed by an average of 33.2%.…”
Section: Comparison Of Results With That Of Other Published Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…Although aluminum-interspaced grids are not used in modern mammography systems, comparison with the results of the study by Chan et al serves as validation of this technique and also lends perspective to why aluminum should not be used. Like Rezentes et al (6), Chan et al (2) reported two different measurement techniques for determining CIF and BF, and the results of both are illustrated in Figure 6. Compared with Chan et al's "transmission" measurement technique, the average difference with our results was 26.9%, and the "phantom" measurement technique differed by an average of 33.2%.…”
Section: Comparison Of Results With That Of Other Published Studiesmentioning
confidence: 89%
“…This very useful graphical tool was adopted in our study, as it represents a simple but elegant format for evaluating the cost-benefit (ie, cost ϭ BF, benefit ϭ CIF) performance of an antiscatter device. As discussed by Chan et al (2), for an ambient SPR 0 level in the absence of a grid, corresponding to S 0 /P 0 (which is a function of the breast thickness, beam energy, and field of view), the CIF and the BF parameters for an ideal grid both become 1 ϩ SPR 0 . Thus, the performance of a grid with 100% primary transmission is represented by a line of unity slope that extends from the origin of the graph at (BF ϭ 1, CIF ϭ 1) to (1 ϩ SPR 0 , 1 ϩ SPR 0 ).…”
Section: Physical Dimensions and Composition Of The Gridsmentioning
confidence: 93%
See 1 more Smart Citation
“…Although grids are widely used during mammography, few data about grid performance are available. Several investigators have used Monte Carlo simulations to compare grid performance and optimize grid design (4)(5)(6)(7)(8), whereas others have inferred performance from scatter-toprimary measurements with a single mammographic unit (9,10) or have evaluated grid performance qualitatively with clinical images, phantom images, or both (7,9,(11)(12)(13). In the present study, we compared the grid performance of four mammographic units.…”
mentioning
confidence: 99%
“…The product of the transmission efficiencies of G1 and G2 is ~17% and is lower than that of anti-scatter grids used in conventional mammography (Chan et al, 1985, Fahrig et al, 1994, Rezentes et al, 1999, Boone et al, 2002). However, this can be substantially improved.…”
Section: Discussionmentioning
confidence: 83%